Reliability-based performance analysis of mining drilling operations through Markov chain Monte Carlo and mean reverting process simulations. (July 2020) - Ugurlu, Omer Faruk; Kumral, Mustafa
In recent years, commodity prices have swiftly decreased, narrowing the profit margin for many mining operations and forcing them to find effective cost management strategies to respond to low prices. Given that equipment is one of the most significant assets of a mining company, efficient equipment utilization has strong potential to reduce costs. This paper focuses on the relationship between the number of available drilling machines based on reliability analysis and the number of holes to be created on a bench of an open pit mining operation. Since equipment availability is random in nature, a range of holes to be drilled corresponding to a specified probability level was determined. To assess the performance of the proposed approach, a case study was carried out using two stochastic modeling techniques. Evolutions of reliabilities of 10 rotary drilling machines over a specific time were simulated by Markov chain Monte Carlo and mean reverting processes, using historical data. Multiple simulations were then used for risk quantification. Results show that the proposed approach can be used as a tool to assist production scheduling and assess the associated risk.